Libya War and Democracy - Adibe, Veronica Ifeyinwa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
There is no doubt that the Libya civil war has been one of the most dreadful war to happen in Africa in the 21st century leaving the country deeply fractured. It started as a protest against the Abu Salim massacre and then resulted to a conflict which quickly felt across the country as revolutionary wave in the region. By May of 2011, the armed conflict between Colonel Gaddafi forces and those who sought for his removal from government has reached a new dimension. During the war, offers for a truce were rejected by the rebels and endeavors by the international community to stop the battle in light of the fact that the plans put forward did exclude the expulsion of Colonel Gaddafi. Libya responded to the protest with military force, threatening to crush any protester. The United Nations produced UNSC resolution 1970 and 1973 calling for a no-fly zone over Libyan airspace and called on states to take mandatory actions to stop the humanitarian crisis in Libya. NATO responded militarily with a coalition of willing states to enforce the resolutions. This study focuses on analyzing the Libya civil war, humanitarian intervention in line with the principles of just war theory and the expected outcome which is democracy. The study also examines the concept of Responsibility to Protect as an obligation of the international community and states to protect civilians irrespective of their location. The quest for democratization was analyzed and the study concluded that Libya has a long way to democratization. The study recommended true reconciliation, strong political, socio-economic and security engagements including the conduct of free, fair and credible election as solutions to the dead end in Libya. Keywords: Libya, Civil War, Humanitarian Intervention, Responsibility to Protect, NATO, Democracy.

ÖZ: Libya İç Savaşı, 21. yüzyılda Kuzey Afrika’da baş gösteren en korkunç savaşlardan biridir ve ülkeye son derece zarar vermiştir. Savaş, Ebu Selim cezaevi katliamı karşıtı gösterilerle başlamış, ardından bölgedeki devrimci dalganın bir parçası olarak ülke genelinde bir ayaklanmaya dönüşmüştür. Albay Kaddafi yönetimindeki güçler ile hükümet karşıtları arasında yaşanan silahlı çatışma, 2011 yılının Mayıs ayında farklı bir boyut kazanmıştır. Çatışma sırasında isyancılar hükümetin ateşkes isteğini ve uluslararası camianın savaşın sona ermesi konusunda gösterdiği bütün gayretleri, öne sürülen planların içinde Albay Kaddafi’nin sınır dışı edilmesi yer almadığı gerekçesiyle reddetmiştir. Libya hükümeti, ayaklanmaya askeri güçle müdahale etmiş ve bütün göstericileri ezip geçmekle tehdit etmiştir. Uluslararası camia, bu savaşa yanıtı Birleşmiş Milletler Güvenlik Konseyi'nin (BMGK) 1970 ve 1973 sayılı kararlarıyla vererek Libya hava sahası üzerinde uçuşa yasak bölge oluşturulması ve Libya’da yaşanan insanlık krizini durdurmak için ne gerekiyorsa yapılması konusunda adım atmıştır. NATO, kararların uygulamaya koyulması için üye ülkelerin de desteğiyle askeri müdahale başlatmıştır. Bu çalışmanın temel odağı, Libya’daki iç savaş ve insani müdahaleyi haklı savaş teorisi ve öngörülen sonuç olan demokrasi bağlamında incelemektir. Bu çalışma, aynı zamanda Koruma Sorumluluğu kavramını uluslararası camianın ve devletlerin, hangi bölgede olursa olsun sivilleri koruma zorunluluğu olarak ele almaktadır. Bu çalışmada demokrasi arayışı incelenmiş ve Libya’nın demokrasi konusunda uzun bir yol kat etmesi gerektiği sonucuna varılmıştır. Bu çalışma, Libya’nın içinde bulunduğu çıkmazı çözebilmek için gerçek anlamda uzlaşma, aynı zamanda özgür, adil ve güvenilir seçimleri kapsayan güçlü siyasi, sosyo-ekonomik ve güvenlik adımlar atılmasını önermektedir. Anahtar Kelimeler: Libya, İç Savaş, İnsani Müdahale, Koruma Sorumluluğu, NATO, Demokrasi.
Master of Arts in Diplomacy and Conflict Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2019. Supervisor: Assist. Prof. Dr. John Albert Turner
Keywords: Political Science and International Relations; Libya--Politics; Civil War--Libya; Libya; Civil War; Humanitarian Intervention; Responsibility to Protect, NATO; Democracy